Creep Mechanical Properties of Granite under Combined Axial Compression and Water Pressure and Support Characteristics of Surrounding Rock. (9th June 2022) - Li, Xiaolong; Zhang, Chong; He, Jianhua; Deng, Xingfu
Abstract : Granite is a common brittle rock material in underground surrounding rock, such as Yebatan Hydropower Station. The underground cavern of Yebatan Hydropower Station has characteristics of large span, high ground stress, fault development, and abundant groundwater. Long-term stability of surrounding rock is a key factor for the project safe operation. Especially for the surrounding rock of large underground cavern, its long-term rheological stability must be considered. In this paper, taking the surrounding rock of a large underground cavern in Yebatan Hydropower Station as research object, creep mechanical test of the combined axial pressure and water pressure under normal water level and dead water level is carried out, and long-term damage mechanism of rock under different water confining pressures is revealed. Based on rock mechanical properties, calculation and analysis of surrounding rock stability under different support time are carried out, and optimal support time is also discussed.